The live talk show: the challenges in pre-production, production and postproduction of 'Apa ke Halnya?' / Nurul Ain Nasis @ Nasirpudin ... [et al.]. - Nasis @ Nasirpudin, Nurul Ain; Cucu Syamsuri, Rita; Anthony Noel Magness, Syafiq; Mohd Zamani, Khir Mukmin; Mohd Jiwahir, Mohd Muhajir (2009)
A live program has been around long before recorded program as the first broadcast was a radio broadcast that existed first. Generally, in television industry, live program is always about news and morning talk show. Talk shows program at first are not very popular in the 90s. But as the world moving forward and the broadcast industry to move ahead into the new era and technology, the whole industry competing each other to produce a reality program that are mostly broadcasted live to the viewers and not surprising, there has been a rapid growth on broadcasting a live talk show where most of it either talking about current issues, social issues, community issues even some of the talk show are made of just for gossiping and wasting time. If there used to be the producer came up with an idea to make a program, nowadays, the celebrities sometime come an idea to make their own talk show. For example, Saturday Night Live, Jimmy Kimmel Live and so forth while in Malaysia, Currently, most of the celebrities talk show are not live broadcasted but else than celebrities talk shows that is discussing the current issues in the morning will be around for a long time in a channel as sometimes, it's like a must for the audience to tune in to their favourite morning talk show as we can take for example, the morning talk show in Malaysia that has been years; The Breakfast Show, Selamat Pagi Malaysia, Malaysia Hari lni and so on.